O trabalho do professor Sylvio Nepomuceno, ajudando a reconstituir a história da educacao matemática, ao tempo de influência do Movimento da Matemática Moderna - Santander, Cristiane Vidouto Brandespim (2008)
The objective of this research was to investigate the contribution of teacher Sylvio de Lima Nepomuceno in the rebuilding of the History of Mathematics Education at the time of influence of the Modern Mathematics Movement (MMM). The choice of this teacher as part of this research is due to the fact he had registered his long experience as a teacher on a collection of textbooks and by his participation in the Research Group for the Teaching of Mathematics on training teachers. The theoretical support was supported in the ideas of authors such as the French researcher André Chervel, 1990 in his article History of school subjects: reflections on a search field and the ideas of Alain Choppin in his article History of books and educational editions: about the state of the art . The textbook, as a source of survey research in the history of school subjects, has an important role in that his analysis allows to see how the authors were appropriated or recommendations of the laws in a given period. We believe that the educational collection analyzed, geared to the ideals of the MMM, although with restrictions of the author, particularly as it referred to methodological issues and language. Sylvio de Lima Nepomuceno, to seek ways to improve was a good model of mathematics teacher, has been working to participate in study groups, of Olympics of Mathematics and production of educational material in this way contributing to the teaching of Mathematics in Brazil